Hospitalised rotavirus gastroenteritis in New Zealand: The laboratory database is a valuable tool for assessing the impact of rotavirus vaccination. Issue 35 (16th August 2017) - Kelly, Matthew J.; Foley, David; Blackmore, Timothy K.
Highlights: A passively collected laboratory dataset can be a useful resource for describing infectious disease epidemiology. Rotavirus vaccine introduction in New Zealand occurred during a period of high community rotavirus rate. Rotavirus vaccine introduction has led to a marked drop in hospitalisations for rotavirus gastroenteritis. National figures based on hospital coding data are likely to significantly under report the true vaccine impact. Abstract: Aim: To assess the impact of the introduction of rotavirus vaccination in New Zealand at a regional and national level, underlining the utility of a passively collected laboratory dataset. Method: Retrospective laboratory data for rotavirus testing from Wellington and Hutt Hospitals from 1 January 2010 to 31 December 2016, matched with hospital admissions data of children under 5 years of age with gastroenteritis primary and secondary coded admissions. The second part of the study examined the national dataset of primary coded hospital gastroenteritis admissions from the same period. Results: Rotavirus testing was performed in 1054 (64.1%) of the 1645 gastroenteritis admissions to Wellington and Hutt Hospitals. Four hundred and nine of these tests (38.8%) were positive. Children who were not given a primary code of gastroenteritis accounted for 5.7% of rotavirus admissions. The estimated annual rotavirus hospitalisation rate in the Hutt and Wellington regions for children under 5 years during the pre-vaccination period was 427.1 per 100, 000. In the post-vaccination period (2015–2016), there was a 94.6% reduction in confirmed rotavirus gastroenteritis hospitalisations with only 8 confirmed cases. The total number of gastroenteritis admissions declined by 51.4%. On a national scale, there was a decline of 34.4% in the average annual number of gastroenteritis admissions and the number of coded rotavirus admissions was 87.1% lower than the pre-vaccination average. Conclusion: The non-restrictive continuous approach to rotavirus testing has provided a detailed description of the epidemiology of rotavirus gastroenteritis hospitalisations in the Wellington and Hutt regions. Rotavirus vaccination introduced on the crest of a peak in rotavirus cases has lead to a marked reduction in the number of admissions with gastroenteritis in New Zealand in the two years following vaccine introduction. The national figures likely underestimate the impact of the vaccine.